Systemic administration of polyphenols from dealcoholized red wine reduces inflammation and bone resorption in established apical periodontitis in male rats - de Oliveira Sales-Junior, Romulo [UNESP]; de Moura Pereira, Bharbara [UNESP]; Ricci, Rafaela [UNESP]; da Silva Machado, Nathália Evelyn [UNESP]; Alvarado, Julissa Denisse Arguello [UNESP]; Carreto, Ana Beatriz [UNESP]; Ervolino, Edilson [UNESP]; Kishen, Anil; Cintra, Luciano Tavares Ângelo [UNESP]; Gomes-Filho, João Eduardo [UNESP] (Elsevier, 2025)
Objective: To analyze the effect of supplementation with dealcoholized red wine on the severity of apical periodontitis after it had been established. Design: Thirty-two male Wistar rats were arranged into four groups: water as control, dealcoholized red wine, red wine, and alcohol. Apical periodontitis was induced by pulp exposure for 30 days when supplementation started and continued daily for 30 days. After the supplementation period, the rats were euthanized, and maxillae and jaws were removed to evaluate the inflammatory response and the bone resorption through microtomographic, histological and immunohistochemical analysis. Statistical tests were applied at 5 % significance. Results: The dealcoholized red wine group demonstrated a significant reduction in bone resorption volume and increase in bone volume fraction and trabecular parameters (p < 0.05). The dealcoholized red wine and red wine groups exhibited mild inflammation compared to the control and alcohol groups that showed moderate and severe inflammation respectively (p < 0.05). The immunoreaction was significantly lower in the dealcoholized red wine group than in the control and alcohol groups for the TNF-α, IL-1β and TRAP cells (p < 0.05). Furthermore, OPG in dealcoholized red wine was similar to red wine and control but higher than in the alcohol group (p < 0.05). Conclusion: Supplementation with dealcoholized red wine in rats decreased inflammation and bone loss in established apical periodontitis. This study highlights the potential of systemic administration of polyphenols from red wine in decreasing inflammation and bone resorption of established apical periodontitis in rats.
Keywords: Apical periodontitis; Bone resorption; Dealcoholized red wine; Inflammation